Cebada cervecera – cultivo con perspectivas para la industria Cervecera, estudios actuales 2018-2022. revisión bibliográfica. - González Mejia, Johnny Francisco (2022)
This research aimed to identify the main research conducted on the cultivation of malting barley in the years 2018-2022 using bibliographic research with the keywords malting barley or beer barley through the Google Scholar platform and the SCOPUS database, with specific objectives consisting of analyzing the scientific production with Harzing's Publish or Perish software using metadata obtained from Google Scholar, as well as, in the SCOPUS database. In addition, it was proposed to analyze the data obtained on scientific production of SCOPUS regarding documents by year, author, affiliation, subject area, funding sponsor, and type of document, and, finally, it was proposed to establish possible authorship networks on malting barley cultivation using the VOSviewer program, from the results obtained it was possible to identify that by using Harzing's Publish or Perish software with the metadata obtained from Google Scholar and the keyword Beer barley, it showed 64 documents, with an index of 130 citations, 32. Fifty citations per year, 2.03 citations per document, 3.06 authors per article, an index h of 8, with an index g of 9, while using the keyword Beer barley showed 33 papers, with an index of 7 citations, 1.75 citations per year, 0.21 citations per document, 2.64 authors per article, an index h of 2 and with index g of 9. While in SCOPUS with the keyword Beer barley, 336 papers were found, with an index of 1994 citations, 498.5 citations per year, 5.93 citations per document, 4.83 authors per article, an index h of 20, and with index g of 30, when using the keyword malting barley, three analyzed records were found, with an index of 1 citation, 0.33 citations per year, 0.33 citations. Likewise, it could be determined that the highest number of documents published in SCOPUS with the proposed topics was in 2021, with 99 papers. The researchers with the highest number of contributions were Becker T and Gastl M with nine published works; of the institutions that have posted the most on the topic of Beer barley, the Techincal University of Munich stood out with 22 documents, the subject with the highest percentage of contributions was Agriculture. Biological Sciences with 34.3%, the entity that has provided significant economic resources for project management and publication has been the National Natural Science Foundation of China. The type of document that has been published the most is unpublished and original scientific articles with 81.6%. Finally, with the support of the VOSviewer software, it has been possible to identify eight authorship networks made up of 67 authors who have published more than three scientific articles. It is recommended to carry out bibliographic reviews from the data obtained before generating projects, writing articles, and books, among other academic contributions. It is also necessary to promote bibliographic managers such as Mendeley and new software such as Harzing's Publish or Perish and VOSviewer to perform bibliometric analysis.